DAMPAK PENYIMPANGAN GENDER DALAM OLAHRAGA: DISKRIMINASI DAN KETIDAKADILAN - Gerol Foekh, Risto; Anita Kumaat, Noortje; Wismanadi, Himawan (Fakultas Ilmu Keolahragaan Unimed, 2024)
Sports have developed very rapidly, but behind this progress, sports are still an arena where gender discrimination and inequality often occur. Gender discrimination in sports is not only related to physical differences, but also includes unequal treatment, which often disadvantages one gender (usually women). This study aims to determine discrimination and injustice in the field due to gender deviations in sports. This study is a conceptual study with a literature study method to analyze the impact of gender deviations in sports, especially related to discrimination and injustice. Using a qualitative approach, data was collected through Google Scholar, by selecting relevant journals published in the last ten years, and considering influential classic literature. The conclusion of this study is that there are 7 types of discrimination and injustice due to gender deviations in sports including inequality in involvement and opportunities, discrimination in access to facilities and resources, significant differences in compensation and recognition, harassment and violence related to gender, inequality in leadership positions and decision-making processes, and negative impacts on mental and psychological health are the main issues that need attention in the world of sports